Which of the following equations is of an ellipse with x-intercepts of (3, 0) and (-3, 0) and y-intercepts at (0, 1) and (0, -1)?

Question

Asked 5/2/2013 6:48:07 AM

Updated 7/5/2014 10:04:00 AM

4 Answers/Comments

This conversation has been flagged as incorrect.

cadence|Points 50|

bonaxle|Points 789|

jen_asuncion|Points 145|

jen_asuncion|Points 145|

thewolf010|Points 1160|

arkaideman|Points 163|

Question

Asked 5/2/2013 6:48:07 AM

Updated 7/5/2014 10:04:00 AM

4 Answers/Comments

This conversation has been flagged as incorrect.

Rating

3

The equation of an ellipse with x-intercepts of (3, 0) and (-3, 0) and y-intercepts at (0, 1) and (0, -1) is x^2/3^2 + y^2/1^2 = 1 or x^2 + 9y^2 = 9.

Added 7/5/2014 9:56:01 AM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [7/5/2014 9:57:16 AM]

3

The correct conic section to fit the equation 49x^2 - 16y^2 = 784 is Hyperbola.

49x^2 - 16y^2 = 784

divided by 784 on both sides the result is:

x^2/16 - y^2/49 = 1

x^2/4^2 - y^2/7^2 = 1 which is the equation for hyperbola.

49x^2 - 16y^2 = 784

divided by 784 on both sides the result is:

x^2/16 - y^2/49 = 1

x^2/4^2 - y^2/7^2 = 1 which is the equation for hyperbola.

Added 7/5/2014 9:58:26 AM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [7/5/2014 10:08:03 AM]

3

x^2 - y = 3

x - y = -3

The first equation - the second equation the result is:

x^2 - x = 6

x^2 - x - 6 = 0

(x - 3)(x + 2) = 0

x = 3 or x = -2

when x = 3,

3 - y = -3, y = 3 + 3 = 6;

when x = -2,

-2 - y = -3, y = -2 + 3 = 1.

The solution for the equation system x^2 - y = 3, x - y = -3 is {3, 6}, {-2, 1}

x - y = -3

The first equation - the second equation the result is:

x^2 - x = 6

x^2 - x - 6 = 0

(x - 3)(x + 2) = 0

x = 3 or x = -2

when x = 3,

3 - y = -3, y = 3 + 3 = 6;

when x = -2,

-2 - y = -3, y = -2 + 3 = 1.

The solution for the equation system x^2 - y = 3, x - y = -3 is {3, 6}, {-2, 1}

Added 7/5/2014 10:03:22 AM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [7/5/2014 10:08:02 AM]

3

b^5*b^8 = b^13

Added 7/5/2014 10:04:00 AM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [7/5/2014 10:07:10 AM]

27,688,691

questions answered

There are no comments.